The Efficacy of Valsalva Maneuver Technique on Pain Reduction During IV Cannulation Among Children - Esraa Shaker Saeed Saeed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Peripheral intravenous cannulation is a common pediatric procedure associated with pain and anxiety. Specific Background: Non-pharmacological approaches such as the Valsalva maneuver have been studied in adults, but evidence in pediatric populations remains limited. Knowledge Gap: There is insufficient clinical evidence regarding the application of the Valsalva maneuver for pain management during intravenous cannulation in children aged 12–18 years. Aims: This study aimed to evaluate the role of the Valsalva maneuver in reducing pain during peripheral intravenous cannulation and compare it with standard care. Results: Using a quasi-experimental design with 100 pediatric patients, pain scores significantly decreased from 2.93 before the maneuver to 1.06 after the procedure (p < 0.001). Greater pain reduction was observed among children without prior cannulation experience, while no significant differences were found based on age or gender. Novelty: This study provides focused clinical evidence supporting the use of the Valsalva maneuver specifically in adolescent pediatric patients during intravenous procedures. Implications: The findings support integrating the Valsalva maneuver into routine pediatric clinical practice as a simple, safe, and cost-effective strategy for procedural pain management. Highlights:• Significant Decrease in Procedural Discomfort Observed After Applying the Breathing Technique• Greater Response Noted Among Participants Without Prior Cannulation Exposure• No Variation Detected Across Demographic Characteristics Such as Age and Sex Keywords: Valsalva Maneuver, Pain Reduction, Peripheral Intravenous Cannulation, Pediatric Patients, Non Pharmacological Intervention.